The Relationship Between Self-Control and Impulsive Buying Tendencies among Cryptocurrency Investors in Bekasi City - Cicip Dimas; Tugimin Supriyadi; Sandra Adetya (Journal of Health and Multidisciplinary Health Studies, 2026)
The development of cryptocurrency investment in Indonesia has driven increased impulsive buying behavior due to the highly volatile market characteristics and easy access to digital transactions. One psychological factor suspected to be related to this behavior is self-control. This study aims to determine the relationship between self-control and impulsive buying tendencies among cryptocurrency investors in Bekasi City. The study used a quantitative approach with a correlational design. The study sample consisted of 97 cryptocurrency investors aged 18–40 years residing in Bekasi City, selected using incidental sampling techniques . The research instruments consisted of a self-control scale based on the theory of Tangney, Baumeister, and Boone and an impulsive buying tendency scale based on the concept of Verplanken and Herabadi. Reliability test results showed a Cronbach's Alpha value of 0.775 for the self-control scale and 0.755 for the impulsive buying tendency scale. Based on the Shapiro-Wilk normality test, the data were not normally distributed, so the hypothesis analysis used Spearman correlation. The analysis results show a significant relationship between self-control and impulsive buying tendencies among cryptocurrency investors in Bekasi City (ρ = 0.603; p < 0.001). This finding indicates a strong correlation between self-control and impulsive buying tendencies in the context of cryptocurrency investment. The research findings are expected to serve as a reference for the development of social psychology studies, particularly regarding digital investment behavior and financial decision-making.